DAnIEL: A User-Friendly Web Server for Fungal ITS Amplicon Sequencing Data - Loos, Daniel; Zhang, Lu; Beemelmanns, Christine; Kurzai, Oliver; Panagiotou, Gianni (Frontiers in Microbiology, 2021)
Trillions of microbes representing all kingdoms of life are resident in, and on, humans holding essential roles for host development and physiology. The last decade over a dozen online tools and servers, accessible via public domain, have been developed for the analysis of bacterial sequences, however, the analysis of fungi is still in its infancy. Here we present a web server dedicated to the comprehensive analysis of the human mycobiome for (i) translating raw sequencing reads to data tables and high-standard figures; (ii) integrating statistical analysis and machine learning with a manually curated relational database; (iii) comparing the user’s uploaded datasets with publicly available from the Sequence Read Archive. Using 1,266 publicly available ITS samples, we demonstrated the utility of DAnIEL web server on large scale datasets and show the differences in fungal communities between human skin and soil sites.